Max Stirner e a construção da individualidade na contemporaneidade - BRITO, Gabriel Nascimento (2022)
This paper investigates the contributions of the author Max Stirner to the contemporary development of the concept of individuality. To this end, it is put forward an investigation on his life and work, especially on his magnum opus, “The Ego and its Own”, asides from biographical work and on commentators, in addition to the contributions by other authors influenced by Max Stirner, from which it is sought to comprehend how the works of the author ought to be read two hundred years after his birth. In the initial chapter, there is an overview of Stirner’s life, presenting his influences and the context in which he was embedded. The second chapter dives into the philosophy of Max Stirner, specially on the writings of his book “The Ego and its Own”, considering his fellow commentators, as well as posterior ones. Ultimately, the third chapter brings into debate the impact of his work among his contemporaries, as well as its unfolding, and how it ought to be interpreted in the contemporaneity. At last, by reading Max Stirner’s work through contemporary eyes, it is clear to see how the diffusion of new ways of living comes from the promotion of the individual expression, which must always be encouraged for the sake of the maximum development of every human being.